Tradisi Makkuluhuwallah dalam Ritual Kematian Suku Bugis - Misbah Hudri; Muhammad Radya Yudantiasa (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
This study examines the local tradition of Buginese tribe community in South Sulawesi that is death ritual, precisely in Tadang Palie village. The death ritual is named Makkuluhuwallah taken from the first verse of Surat al-IkhlÄs. The surat is usually recited about 15,000 times to 100,000 times in seven days. The uniqueness of Makkuhuwallah is the medium used to calculate the number of recitations by using gravel. After a seventh day, the pebbles will be placed above the grave or gravestone. This research type is qualitative research which its data processing system used is descriptive-analytic. The working instrument combines library studies and field studies. This study also wants to see how the Qur'an is responded by a popular society with the term Living Qur'an Study. The author finds the reason behind the use of the surah al-IkhlÄs in Makkuluhuwallah procession. It is based on the public receptions of al-IkhlÄs. Surat al-IkhlÄs includes the shortest letter in the Qur'an and has a great prominence (faá¸Ä«lah). The prominence of al-IkhlÄs is often found in a hadith which states that reciting surat al-IkhlÄs is equal with the whole of the Qur'an. Logically, reciting al-IkhlÄs three times already completes the whole al-Quran especially when reciting it thousand times. The writer suspects that motivation is the basis of the implementation of Makkuluhuwallah.